2004
DOI: 10.5703/1288284313134
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Cost Overruns and Time Delays of INDOT Projects

Abstract: Prepared in cooperation with the Indiana Department of Transportation and Federal Highway Administration. AbstractA commonality among state Departments of Transportation is the inability to complete projects on time and within budget. This project assessed the extent of the problem of cost overruns, time delays, and change orders associated with Indiana Department of Transportation (INDOT) construction projects, identified the reasons for such problems, and finally developed a set of recommendations aimed at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 0 publications
4
71
0
4
Order By: Relevance
“…Some of these studies are described as follows. Bordat et al (2004) found that project type, location, weather, difference between first and second lowest bids, difference between engineer's estimate and lowest bid, and project duration were significant factors that explained cost overrun in Indiana during the period 1996-2001. In a subsequent study, ordinary least square regression models were developed to predict cost overrun as a function of these projectspecific factors.…”
Section: Step 5: Development Of Risk-based Econometric Analysis Framementioning
confidence: 99%
See 1 more Smart Citation
“…Some of these studies are described as follows. Bordat et al (2004) found that project type, location, weather, difference between first and second lowest bids, difference between engineer's estimate and lowest bid, and project duration were significant factors that explained cost overrun in Indiana during the period 1996-2001. In a subsequent study, ordinary least square regression models were developed to predict cost overrun as a function of these projectspecific factors.…”
Section: Step 5: Development Of Risk-based Econometric Analysis Framementioning
confidence: 99%
“…Non-preventable change orders occur due to changed field conditions, failed materials, or changes in standards or specifications. Bordat et al (2004) analyzed 822 contracts implemented in 1996-2001 and found that of the total amount associated with change orders ($65 Million), the design-related errors and omissions were responsible for 15% ($9.5 Million) and the constructability of the design was found responsible for approximately 5% ($3.4 Million). Inadequate time to produce quality designs and no accountability for project's construction performance are the two reasons that were cited as root causes for design errors and omissions.…”
Section: Estimation Of Design Cost At Highway Agenciesmentioning
confidence: 99%
“…A significant amount of past research in PPP projects for roadway construction and preservation has focused on the identification of factors affecting cost savings, cost overrun, time delays, and change orders (Rowland, 1981;Hester et al, 1991;Majid and McCaffer, 1998;Jacoby, 2001;Ellis and Thomas, 2003;Fimpong et al, 2003;Flyvbjerg et al, 2003;Bordat et al, 2004;Odeck, 2004;Assaf and Al-Hejji, 2006;Gkritza and Labi, 2008;Anastasopoulos et al, 2010aAnastasopoulos et al, ,b,c, 2011Anastasopoulos et al, , 2014Serag et al, 2010;Ambituuni, 2011;Irfan et al, 2011;Cantarelli et al, 2012). For example, Odeck (2004) formulated a regression framework to investigate the factors affecting cost overrun in roadway construction projects and found that small-scale projects are more vulnerable to cost overrun.…”
Section: Review Of Past Workmentioning
confidence: 99%
“…Project cost and time discrepancies constitute contractual aberrations of high interest to both public and the private entities, and typically include cost overrun, cost savings, change orders, and time delays (Bordat et al, 2004). Previous research has been devoted on the investigation of the influential factors for each of the aforementioned project discrepancies, independently of the PPP type.…”
mentioning
confidence: 99%
“…Delay is defined as the difference between the estimated scheduled final date and the actual final date of project stages (Bordat, McCullouch, & Sinha, 2004). Delays in construction projects have been a research topic for a long time.…”
Section: Causes and Effects Of Delays In Construction Projectsmentioning
confidence: 99%